2014
DOI: 10.1007/s00415-014-7481-x
|View full text |Cite
|
Sign up to set email alerts
|

Costeff syndrome: clinical features and natural history

Abstract: Costeff syndrome (CS) is a rare autosomal-recessive neurological disorder, which is known almost exclusively in patients of Iraqi Jewish descent, manifesting in childhood with optic atrophy, ataxia, chorea and spastic paraparesis. Our aim was to study the clinical spectrum of CS and natural history using a cross-sectional study design. Consecutive patients with CS were recruited to the study. Patients were diagnosed based on clinical features, along with elevated urinary levels of methylglutaconic and methylgl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Costeff syndrome, also known as type III 3-methylglutaconic aciduria, is caused by autosomal recessive OPA3 mutations and, to date, has been reported almost exclusively among patients of Iraqi-Jewish descent (Yahalom et al 2014). Patients with Costeff syndrome usually present with early-onset bilateral optic atrophy, later-onset spasticity, extrapyramidal dysfunction, cerebellar ataxia, and mild cognitive defect (Anikster et al 2001; Sofer et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Costeff syndrome, also known as type III 3-methylglutaconic aciduria, is caused by autosomal recessive OPA3 mutations and, to date, has been reported almost exclusively among patients of Iraqi-Jewish descent (Yahalom et al 2014). Patients with Costeff syndrome usually present with early-onset bilateral optic atrophy, later-onset spasticity, extrapyramidal dysfunction, cerebellar ataxia, and mild cognitive defect (Anikster et al 2001; Sofer et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…37 Recently, we described the clinical features and natural history of 28 patients with CS. 36 Chorea and ataxia did not seem to worsen significantly with age. Pyramidal signs and spastic paraparesis developed later, progressed continuously, and significantly contributed to ambulation difficulties.…”
Section: Opa3-related Choreamentioning
confidence: 75%
“…30,[33][34][35] The disease usually presents with hypotonia, developmental delay, chorea, and mild ataxia in the first year. 29,31,36 The extrapyramidal movements can be very severe and thus prevent motor skill achievements. 37 Recently, we described the clinical features and natural history of 28 patients with CS.…”
Section: Opa3-related Choreamentioning
confidence: 99%
“…Given that the processes of longitudinal bone growth and skeletal remodelling are remarkably similar in rodents and humans (50), our data have significant implications for individuals with Costeff syndrome. Although evidence has recently emerged of limb dystonia (51,52) and ataxia (52,53), there do not appear to be any extant studies of skeletal development, bone microarchitecture or fracture risk in the identified Costeff syndrome kindreds. Although it is possible that the skeletal impairment in the Opa3 L122P mice relates to the specific mutation in this model, Costeff syndrome has been reported in humans with mutations in exon2 of Opa3 (19,23).…”
Section: Discussionmentioning
confidence: 99%